Bald Eagle (Haliaeetus leucocephalus) Feathers as an Alternative to Blood for Microsatellite DNA Analysis: Toward a Non–invasive Technique for Conservation Genetics - Courchesne, Sarah; Meola, Dawn; Alcivar–Warren, Acacia (Wildlife Rehabilitation Bulletin, 2005)
The bald eagle (Haliaeetus leucocephalus) is currently classified as threatened in the lower 48 United States. In Massachusetts, only 12 active nesting sites presently exist, and the majority of breeding birds originated from a population of eaglets imported from Nova Scotia in the 1980s. Previous work using Random Amplified Polymorphic DNA (RAPD) technique demonstrated a genetic diversity among Massachusetts’s eagles of only 22 percent. RAPD, while useful for genetic analysis of blood samples, proved to be inappropriate for analysis of feather samples from the same birds. To address this, our current work aimed at determining whether microsatellites would yield identical information for blood and feather samples from the same animal. Utilizing GenBank sequences, a total of 24 microsatellite primer sets representing 18 loci were designed and tested for allele polymorphism using DNA from eight blood samples and a single annealing temperature in the polymerase chain reaction (PCR). Thirteen microsatellites (54%) representing 11 loci were polymorphic, and three of these were selected to compare allele sizes in blood and feather DNA from the same eaglet. Preliminary results using microsatellite AJ620425 showed that 18 out of 44 blood/feather pairs amplified alleles of similar sizes. Feather DNA of the other 26 blood/feather pairs tested did not amplify any alleles. Data suggest that microsatellite alleles from blood and feather of the same bird may be consistent, and the microsatellite technique could be useful for non–invasive conservation genetics studies. However, multiple repetitions of the experiment are needed in order to determine optimum DNA concentration for feather samples. Additionally, refinements to the protocol will be necessary to obtain greater amplification of feather DNA which tended to give somewhat weak signals.